A comparative study of fluorescent microscopy with Ziehl-Neelsen staining and culture for the diagnosis of pulmonary tuberculosis - Laifangbam, S; Singh, HL; Singh, NB; Devi, KM; Singh, NT (Kathmandu University Medical Journal, 2010)
Background: For developing countries with a large number of cases and financial constraints, evaluation of rapid and inexpensive diagnostic methods has great importance. The bacilli in the sputum can be detected microscopically by ZN stain and fluorochrome stain. Objectives : To study the efficacy of fluorescence microscopy in the diagnosis of pulmonary tuberculosis in comparison to Ziehl-Neelsen staining and culture of sputum samples from patients suspected of pulmonary tuberculosis. Materials and methods : 306 sputum samples collected from 102 patients suspected of pulmonary tuberculosis were processed by the Petroff's method, and subjected to Ziehl-Neelsen staining (ZN), fluorescent Auramine-O staining (AO) and culture on modified Lowenstein-Jensen media (gold standard) for detection of Mycobacterium tuberculosis. Positive smears were graded according to Forbes BA et al, and culture isolates were biochemically tested for confirmation of species. Results : Out of 102 patients, 44.1%, 71.6% and 70% were found positive by ZN, AO and culture respectively. AO was found to be superior to ZN on several aspects. The difference in their case detection rates was statistically significant (χ2 = 24.93, p < 0.001). AO was also able to detect more pauci-bacillary cases than ZN. There was more agreement between culture and fluorescence microscopy (95.1%) than with ZN microscopy (69.6%). The percentage of false negative by AO staining was only 2.78% which was in sharp contrast to that of ZN (40.27%). Conclusion: The better case detection rates of AO over ZN were comparable to those found by several studies. Since screening was done under lower power of magnification (400x), fluorescence microscopy has been found to be less time consuming as compared to ZN method (1000x) in the diagnosis of tuberculosis. The tubercle bacilli stood out as bright objects against a dark background in fluorescence microscopy which makes them easily identifiable hence causing less eye-strain. The efficacy of fluorescence microscopy proved to be much higher than conventional light microscopy and comparable to that of culture. Key words: Ziehl-Neelsen staining; Mycobacterium tuberculosis; Auramine-O DOI: 10.3126/kumj.v7i3.2728 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 226-230